DICER1-associated Tumors in the Female Genital Tract: Molecular Basis, Clinicopathologic Features, and Differential Diagnosis. (1st September 2022) - Han, Lucy M.; Weiel, Julianna J.; Longacre, Teri A.; Folkins, Ann K.
Abstract : DICER1 syndrome is a tumor predisposition syndrome in which patients are at an increased risk of developing a wide variety of benign and malignant neoplasms with a hallmark constellation of pediatric pleuropulmonary blastoma, cystic nephroma, and thyroid lesions. DICER1 encodes an RNA endoribonuclease that is crucial to the processing of microRNA and may play a role in the maturation of Müllerian tissue. Within the gynecologic tract, germline mutations in DICER1 are associated with an array of rare tumors, including Sertoli-Leydig cell tumor, embryonal rhabdomyosarcoma of the cervix, gynandroblastoma, and juvenile granulosa cell tumor, which typically present in childhood, adolescence, or early adulthood. In addition, somatic DICER1 mutations have been described in rare gynecologic tumors such as adenosarcoma, Sertoli cell tumor, ovarian fibrosarcoma, cervical primitive neuroectodermal tumor, carcinosarcoma, and germ cell tumors. In light of the significant association with multiple neoplasms, genetic counseling should be considered for patients who present with a personal or family history of these rare DICER1-associated gynecologic tumors. This review highlights the most current understanding of DICER1 genetic alterations and describes the clinical, histopathologic, and immunohistochemical features and differential diagnoses for gynecologic tumors associated with DICER1 mutation.